Effects of planting method on yield and yield attributing characters in chickpea (Cicer arietinum L.) - Alam, MS; Haydar, FMA; Hoque, A (Journal of Bio-Science, 2019)
The experiment was conducted to study the effect of planting method on yield and yield attributing characters in chickpea. A randomized complete block design was adopted for the experiment with three replications. Four variety viz. BAU-1, BINA Chola-4, BINA Chola-5 and BINA Chola-9 and two planting method i.e. line sowing and ridge sowing were used in the experiment. The highest seed yield (1.81 ton/ha) was obtained from BINA Chola-4 and the lowest one (1.31 ton/ha) was found in BARI Chola-9. The seed yield was higher in ridge sowing (1.57ton/ha) and the lower (1.53 ton/ha) in line sowing. The highest seed yield (1.83 ton/ha) was obtained from BINA Chola-4 with ridge sowing and the lowest (1.30 ton/ha) was obtained from BARI Chola-9 in line sowing. It is concluded that ridge sowing is better than line sowing for the yield of chickpea. J. bio-sci. 28: 105-110, 2020